2022
DOI: 10.1002/adma.202203915
|View full text |Cite
|
Sign up to set email alerts
|

A pH‐Responsive Cluster Metal–Organic Framework Nanoparticle for Enhanced Tumor Accumulation and Antitumor Effect

Abstract: As a result of the deficient tumor‐specific antigens, potential off‐target effect, and influence of protein corona, metal–organic framework nanoparticles have inadequate accumulation in tumor tissues, limiting their therapeutic effects. In this work, a pH‐responsive linker (L) is prepared by covalently modifying oleylamine (OA) with 3‐(bromomethyl)‐4‐methyl‐2,5‐furandione (MMfu) and poly(ethylene glycol) (PEG). Then, the L is embedded into a solid lipid nanoshell to coat apilimod (Ap)‐loaded zeolitic imidazola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…Microfluidic technology with high precision and controllability has been widely used to prepare multifunctional microparticles or microcapsules for various biomedical applications including drug/cell delivery, cell culture, and tissue engineering [ [27] , [28] , [29] , [30] , [31] , [32] ]. Especially, the resultant microparticles or microcapsules with tunable sizes, dispersity, structures, and components could be employed as delivery systems of multimodal tumor therapy [ [33] , [34] , [35] , [36] ]. Although with many successes, the generation of most of these polymer microcarriers often requires additional extra initiators.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic technology with high precision and controllability has been widely used to prepare multifunctional microparticles or microcapsules for various biomedical applications including drug/cell delivery, cell culture, and tissue engineering [ [27] , [28] , [29] , [30] , [31] , [32] ]. Especially, the resultant microparticles or microcapsules with tunable sizes, dispersity, structures, and components could be employed as delivery systems of multimodal tumor therapy [ [33] , [34] , [35] , [36] ]. Although with many successes, the generation of most of these polymer microcarriers often requires additional extra initiators.…”
Section: Introductionmentioning
confidence: 99%
“…3 and 5 . Furthermore, both in vitro and in vivo studies demonstrated that OX@Se-MnP NPs are taken up by colorectal cancer cells and continue to generate ·OH via a Fenton-like catalytic reaction, subsequently triggering caspase-mediated tumor apoptosis[ 62 ]. Thus, Se-MnP NPs function synergistically with OX to induce apoptosis in vitro and suppress tumor growth in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Microfluidic technology, as one of the most promising technologies, can well integrate the nanoparticle synthesis platform into a small glass chip, rendering the synthesis of nanoparticles more controllable [ 26 ]. In general, the small size of nanoparticles, their large specific surface area, and their quantum size effect endow them with special properties lacking in conventional materials [ 27 ].…”
Section: Resultsmentioning
confidence: 99%